2001
DOI: 10.1002/joc.613
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the daily intensity of precipitation in Italy from 1951 to 1996

Abstract: An analysis of 67 sites of daily precipitation records over the 1951-1996 period for Italy is presented. Seasonal and yearly total precipitation (TP), number of wet days (WDs) and precipitation intensity (PI) are investigated, and the trends both for the single station records, and for some different area average series are studied. PI is analysed by attributing precipitation to ten class-intervals, removing the influence of variations in the number of WDs to yield changes in the underlying shape of the WD amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 41 publications
11
148
0
5
Order By: Relevance
“…A change point in 1931 marks a shift in the NAO from being predominantly positive up to this point to increasingly negative until the 1960s (Figure 3). A change point in the 1970s is associated with a trend towards more positive NAO values and has been the subject of much previous research (Bardossy and Caspary, 1990;Smith, 1995;Vincent and Vallon, 1997;Weber, 1997;Hoppe and Kiely, 1999;Kiely, 1999;Werner et al 2000;Brunetti et al, 2001). The change point in 1980 is identified as having the highest probability (0.87) of the four change points identified, the timing of which is consistent with the findings of Hurrell (1995).…”
Section: Identification Of Change Pointssupporting
confidence: 68%
See 1 more Smart Citation
“…A change point in 1931 marks a shift in the NAO from being predominantly positive up to this point to increasingly negative until the 1960s (Figure 3). A change point in the 1970s is associated with a trend towards more positive NAO values and has been the subject of much previous research (Bardossy and Caspary, 1990;Smith, 1995;Vincent and Vallon, 1997;Weber, 1997;Hoppe and Kiely, 1999;Kiely, 1999;Werner et al 2000;Brunetti et al, 2001). The change point in 1980 is identified as having the highest probability (0.87) of the four change points identified, the timing of which is consistent with the findings of Hurrell (1995).…”
Section: Identification Of Change Pointssupporting
confidence: 68%
“…A number of studies have identified a change point in climate as having occurred during the early 1970s (Hoppe and Kiely, 1999;Kiely, 1999) resulting in increases in precipitation in Ireland (Kiely, 1999) and Scotland (Smith, 1995), a change in the meteorological controls of Glacier de Sarennes during the ablation season (Vincent and Vallon, 1997), increasing precipitation intensity in Italy (Brunetti et al, 2001), increasing temperature at 300 hPa in the lower and middle latitudes (Weber, 1997) and increasing 700 mb heights over western Canada (McCabe and Fountain, 1995). This period also corresponds with a shift in the seasonal zonal frequency over Europe as outlined by Bardossy and Caspary (1990).…”
Section: Introductionmentioning
confidence: 99%
“…A suitable approximation for daily precipitation data is given by the gamma distribution, which allows a compact description of the entire distribution by two parameters (Groisman et al, 1999(Groisman et al, , 2005Brunetti et al, 2001;Voss et al, 2002). We have chosen to base our analysis on the gamma distribution to give a uniformly rigorous and systematic approach.…”
Section: Methodsmentioning
confidence: 99%
“…In order to understand changes in the observed precipitation as an indicator of climate changes, daily precipitation series must be analysed (Jones et al, 1999;Karl et al, 1999;Brunetti et al, 2001). The analysis of daily precipitation in the Iberian Peninsula has received scarce attention, probably because of the lack of highquality daily data.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Goodess and Jones (2002) for the Iberian Peninsula show a tendency towards more, less-intensive rain across much of Iberia, with a tendency towards days of increasingly intensive rain along the southeastern Mediterranean coast. Brunetti et al (2000Brunetti et al ( , 2001 detected positive trends for rainfall intensity for several gauges in northeastern Italy. These positive trends are due to an increase in extreme precipitation.…”
Section: Time Trendsmentioning
confidence: 95%